Как-то я летел с рябины: Стихи / Артур Гиваргизов ; худ. : М. Яснова - Гиваргизов Артур Александрович (Стих и Штрих, 2011)
Экземпляры: (20140430) / Инвентарный номер: 47641 / Цена: 319.00 / Сис.шифр: Р 2 / Авт.знак: Г 46 / ББК: 84(2Рос-Рус)6-5